Application of flow diverters in the treatment of aneurysms in the internal carotid artery bifurcation region. Issue 4 (August 2020) - Mahmoud, Mostafa; Farag, Ahmed; Farid, Mostafa; Elserwi, Ahmed; Abdelsamad, Amr; Guergues, Wessam; Hassan, Farouk
Introduction: The treatment of aneurysms in the internal carotid bifurcation region (ICABR), including aneurysms of the true internal carotid artery (ICA) terminus, those inclined on the proximal A1 or M1 segments or at the most distal pre-bifurcation (ICA) segment, is often challenging in microsurgical clipping and endovascular surgery. Few reports had discussed flow diversion as a therapeutic option for this group. Methods: This was a retrospective study analysing flow diversion in treating ICABR aneurysms. Seven patients harbouring eight aneurysms in the ICABR were treated with flow diversion. Five aneurysms were inclined on the proximal A1 segment, and three were located at the most distal pre-bifurcation segment. Patients' demographics, presentation, procedure technical description, angiographic and clinical follow-up were recorded. PubMed and Ovid MEDLINE were also reviewed for articles published in English, including case series or case reports, for ICABR aneurysms treated with flow diverters. Results: All patients except one underwent angiographic follow-up. The Karman–Byrne occlusion scale was used to determine the occlusion rate. All six patients with documented angiographic follow-up had a class IV occlusion score. No permanent or transient neurological or non-neurological complications were encountered in this study. Conclusion: Treating ICABR aneurysms using flow diversion is feasible, with a promising angiographic occlusion rate. Further studies are needed to analyse long-term clinical and angiographic results.